Study of Protein Conformational Dynamics Using Hydrogen/Deuterium Exchange Mass Spectrometry - Uhrik, Lukas; Henek, Tomáš; Planas-Iglesias, Joan; Kucera, Josef; Damborsky, Jiri; Marek, Martin; Hernychova, Lenka (Methods in molecular biology, 2023)
Intrinsic protein dynamics contribute to their biological functions. Rational engineering of protein dynamics is extremely challenging with only a handful of successful examples. Hydrogen/deuterium exchange coupled to mass spectrometry (HDX-MS) represents a powerful technique for quantitative analysis of protein dynamics. Here we provide a detailed description of the preparation of protein samples, collection of high-quality data, and their in-depth analysis using various computational tools. We illustrate the application of HDX-MS for the study of protein dynamics in the rational engineering of flexible loops in the reconstructed ancestor of haloalkane dehalogenase and Renilla luciferase. These experiments provided unique and valuable data rigorously describing the modification of protein dynamics upon grafting of the loop-helix element. Tips and tricks are provided to stimulate the wider use of HDX-MS to study and engineer protein dynamics.
Keywords: Mass Spectrometry; deuterium; konformace proteinů; hmotnostní spektrometrie; Deuterium; Hydrogen; vodík-deuteriová výměna; vodík/deuteriová výměna a hmotnostní spektrometrie; vodík; Protein Conformation; Deuterium Exchange Measurement; Hydrogen Deuterium Exchange-Mass Spectrometry